1998
DOI: 10.1242/jcs.111.20.3027
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome dynamics in early embryos of Caenorhabditis elegans

Abstract: The early Caenorhabditis elegans embryo divides with a stereotyped pattern of cleavages to produce cells that vary in developmental potential. Differences in cleavage plane orientation arise between the anterior and posterior cells of the 2-cell embryo as a result of asymmetries in centrosome positioning. Mechanisms that position centrosomes are thought to involve interactions between microtubules and the cortex, however, these mechanisms remain poorly defined. Interestingly, in the early embryo the shape of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It has previously been shown that, guided by cell-cell contact with the posterior P1 cell (Fig. 1A), the AB cell initially sets up the mitotic spindle in the plane orthogonal to the AP axis [44][45][46] (the dorsal-ventral leftright, or DV-LR plane, Fig. 1A).…”
Section: Mainmentioning
confidence: 97%
“…It has previously been shown that, guided by cell-cell contact with the posterior P1 cell (Fig. 1A), the AB cell initially sets up the mitotic spindle in the plane orthogonal to the AP axis [44][45][46] (the dorsal-ventral leftright, or DV-LR plane, Fig. 1A).…”
Section: Mainmentioning
confidence: 97%